Sífilis tardía. Reporte de un caso. - ZEGARRA P, Jaime (2013)
A 48 year-old male presented with a 6 month history of a dementia syndrome, memory deficit, impairment of judgement, and right sligth hemiplegia, and sexual promiscuity. ELISA for HIV was negative; the VDRL and FTA-abs for syphilis were positive (1/8 and 3+ respectively); VDRL int the CSF was positive (1/8) making the diagnosis of neurological syphilis. In addition, significant NMR images are presented. The patient received penicilin I.V. with clinical, neurological and radiological improvement.